Design of a Modified Bituminous Binder with Polypropylene Membranes and Polymers Considering Extreme Temperature Variations in Chimborazo - Bejarano-Chaguancallo, Vanesa (2023)
The purpose of this research was to add polypropylene membranes with polymers for the design of a modified binder that behaves adequately in extreme temperature changes in the province of Chimborazo. For its development, an AC-20, SBR and PP asphalt binder was used as a base; through the state of the art, five samples named A, B, C, D and E were elaborated, and finally, conventional characterization and performance grade tests were carried out. Also, information on maximum and minimum temperatures recorded in the province of Chimborazo during the last 10 years was obtained from INAMHI and the Development and Land Management Plan. The data obtained determined that the sample modified with 0.5% PP and 1% SBR presents the best results considering physical characteristics and performance in extreme temperatures, because the increase of 14.90% in the flash point and 5.4% in the fault temperature with respect to the conventional binder AC-20; increased deformation at the requested loads, a decrease of 53.17% in its rigidity at a temperature of -10°C. On the other hand, from the climatic variation of Chimborazo and based on the LTPP algorithm, it was determined that the maximum and minimum temperature of the pavement is 58.50°C and -3.18°C respectively. The addition of 0.5% PP and 1% SBR improved the physical and rheological properties of the conventional binder; therefore, its use in the province of Chimborazo is appropriate.